Analysis of the fundamental absorption edge of the films obtained from the C₆₀ fullerene molecular beam in vacuum and effect of internal mechanical stresses on it - Kolyadina, E.Yu.; Matveeva, L.A.; Neluba, P.L.; Venger, E.F. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2015)
Nanostructures with fullerene C₆₀ were obtained using vacuum sublimation thermal C₆₀ fullerene powder onto unheated substrates made of silicon, mica, silica and coverslip glass. The effect of the structure, composition and mechanical stresses in the films on fundamental absorption, density-of-states tails in them were investigated by Ramаn spectroscopy, atomic force microscopy, light absorption, electroreflectance modulation spectroscopy and measuring the bend of heterosystems. Ascertained in this work has been the origin of variation observed in literature data concerning the width of the band gap Eg between 1.48 to 2.35 eV and the nature of the fundamental absorption edge in solid C₆₀. This variation is related with decomposition of fullerene molecules caused by the increase in temperature of sublimation. It has been found that C₆₀ in the crystalline state is direct band-gap semiconductor with Eg close to 1.6 eV in the singular point X of the Brillouin zone. The electroreflectance spectra of films and heterosystems bending were used to calculate the Eg dependence on the internal mechanical stresses. The respective coefficient value is equal to –2.8 10⁻¹⁰ eV/Pa.